Determining Factors for Sharia Stock Investment Decisions that Have An Impact on Value Recovery Companies During A Pandemic - Supitriyani Supitriyani; Musa Fernando Silaen; Marto Silalahi (Center for Risk Management & Sustainability and RSF Press, 2022)
Due to the company's ongoing global expansion, numerous investors are competing to invest their money in it. The purpose of this is to get ready for the future. The stock prices of numerous companies have fallen as a result of the COVID-19 pandemic. But this actually causes Islamic stocks to rise gradually until they finally experience an increase in investors each year. In order to help investors who are considering investing in sharia-based companies, this study aims to test the effects of the determinants of the determinants of Sharia stock investment decisions on company value. Purposive sampling with non-probability sampling was used for the sampling technique. The method used for quantitative descriptive analysis in this study is multiple linear regression analysis. The conclusions in this study show that investment opportunities, profitability, debt policy and dividend policy have a significant effect on the value of the company simultaneously and partially the investment opportunity, profitability and debt policy have a significant effect on the value of the company while the dividend policy does not have a significant effect on the value of the company in the Jakarta Islamic Index.